Barriers to Somatic Health Care for Persons With Severe Mental Illness in Belgium: A Qualitative Study of Patients' and Healthcare Professionals' Perspectives - Kohn, Laurence; Christiaens, Wendy; Detraux, Johan; De Lepeleire, Jan; De Hert, Marc; Gillain, Benoit; Delaunoit, Benjamin; Savoye, Isabelle; Mistiaen, Patriek; Jespers, Vicky (Frontiers in Psychiatry, 2022)
Background: A huge and still growing mortality gap between people with severe mental illness (SMI) and the general population exists. Physical illnesses, mainly cardiovascular diseases, substantially contribute to the high mortality rates in patients with SMI. Disparities in somatic health care access, utilisation, and provision contribute to these poor physical health outcomes. Methods: A qualitative study, using semi-structured interviews, was set up to explore SMI patients’ and healthcare professionals’ perspectives on somatic health care in different psychiatric settings of the three Belgian regions (Flanders, Brussels, Wallonia). Interviews were digitally recorded and transcribed prior to qualitative inductive thematic analysis, using Nvivo software. The COnsolidated criteria for REporting Qualitative research (COREQ) were used for reporting methods and findings. Results: Collaboration and information flows between psychiatric healthcare professionals, non-psychiatric healthcare professionals, and persons with SMI were troublesome. This seemed to be mainly due to stigma and prejudice and challenging communication and data transfer. Lack of sufficient training and experience to identify and treat somatic health problems in people with SMI (for psychiatrists and psychiatric nurses) and lack of psychiatric knowledge and feeling or sensitivity for psychiatric patients (for non-psychiatric healthcare professionals) further complicated adequate somatic health care. Finally, optimal somatic follow-up of patients with SMI was hampered by organisational problems (unavailability of equipment, unadapted infrastructure, understaffing, hospital pharmacy issues, and insufficient health promotion/lifestyle interventions), patient-related issues (unawareness of physical problems, non-adherence, need for accompaniment) and financial barriers. Conclusion: There is an urgent need for integrated somatic and mental healthcare systems and a cultural change. Psychiatrists and primary care providers continue to consider the mental and physical health of their patients as mutually exclusive responsibilities due to a lack of sufficient training and experience, poor or absent liaison links, time constraints and organisational and financial barriers. Modifying these aspects will improve the quality of somatic health care for these vulnerable patients.